A STUDY OF THE CONSTRUCTION AND LEVEL OF ENVIRONMENTAL FRIENDLINESS OF THE MINI PURSE SEINE FISHING GEAR AT THE FISHING PORT OF THE ARCHIPELAGO SUNGAILIAT PROVINCE OF BANGKA BELITUNG - Sagala, Ade Putra; Rengi, Pareng; Hutauruk, Ronald (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTÂ This study aims to determine the size and construction specifications of mini purse seine fishing gear, the level of environmental friendliness and how much bycatch and discard. analysis of the data used according to FAO (1995) in accordance with the standard Code of Conduct for Responsible Fisheries (CCRF) which is there are 9 criteria for a fishing gear said to be environmentally friendly.The sample of this research is a mini purse seine fishing gear that operates in PPN Sungailiat. Data collection was carried out by questionnaire distributed directly to 18 respondents. The method used is the survey method by conducting direct interviews with fishermen.the results of this study indicate that this fishing gear is included in the environmentally friendly fishing gear of each Gt of a ship with a score of 27.28 for a vessel size of 10 gt, 28.33 for a ship size of 20 gt and 26.00 for a size of 30 gt. There are 7 types of catch including 3 types included in the main catch and 4 types of bycatch.Â keywords: Environmental friendliness, mini purse seine, main catch and bycatch